INDUCTION OF UTERINE EVACUATION WITH INTRA-AMNIOTIC PROSTAGLANDIN F2-ALPHA - Huamán, Moisés (2015)
In 14 pregnant inducing uterine evacuation it was conducted using Prostaglandin F2-alpha, administered by trans-abdominal puncture under ultrasound guidance in amniotic cavity. 73 cases had ultrasound diagnosis of fetal death, 1 patient had multiple malformations (acranea, etc.) and 9 were severe hypertensive disease. 42.1% were primiparous and 78.5% nulliparous. All had closed cervix. Gestational age ranged between 20 and 39 weeks and uterine height between 04 and 26 cm. The average dose of PGF-2 alpha used was 7.5 mg. (5 to 10 mg.); not greater volume of amniotic fluid was extracted. Uterine evacuation occurred in 100% of cases, between 2-73 hours after (average 6.2 hours). In 2 cases after curettage evacuation it was made. There was one case of nausea, vomiting, and hypotension. We conclude that the use of intra-amniotic PGF2-Alpha gives excellent results in uterine evacuation.